2018
DOI: 10.3389/fpls.2018.00062
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic Treatment of Nicotiana benthamiana with Kifunensine Modifies the N-glycans of Recombinant Glycoprotein Antigens to Predominantly Man9 High-Mannose Type upon Transient Overexpression

Abstract: Nicotiana benthamiana transient overexpression systems offer unique advantages for rapid and scalable biopharmaceuticals production, including high scalability and eukaryotic post-translational modifications such as N-glycosylation. High-mannose-type glycans (HMGs) of glycoprotein antigens have been implicated in the effectiveness of some subunit vaccines. In particular, Man9GlcNAc2 (Man9) has high binding affinity to mannose-specific C-type lectin receptors such as the mannose receptor and dendritic cell-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 69 publications
3
20
0
1
Order By: Relevance
“…The 42 kDa band disappeared when the expressed product was subjected to β-elimination treatment known to remove sugars O-linked to Ser/ Thr 42 . When N-glycosylated cholera toxin B subunit (gCTB) was transiently expressed in N. benthamiana leaves, Western blot analysis of the expressed protein without glycosidase treatment showed two distinct bands 43,44 . The band with the higher molecular weight corresponds to the glycosylated form of gCTB whereas another band represents the aglycosylated form 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The 42 kDa band disappeared when the expressed product was subjected to β-elimination treatment known to remove sugars O-linked to Ser/ Thr 42 . When N-glycosylated cholera toxin B subunit (gCTB) was transiently expressed in N. benthamiana leaves, Western blot analysis of the expressed protein without glycosidase treatment showed two distinct bands 43,44 . The band with the higher molecular weight corresponds to the glycosylated form of gCTB whereas another band represents the aglycosylated form 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a whole-plant study, Roychowdhury et al have shown that the yield of recombinant cholera toxin B subunit dropped by 30% and 75% when kifunensine was supplied at 5 µM hydroponically for 3 days and 5 days post agroinfiltration, respectively [ 16 ]. In contrast, we observed slight increase in protein yield when kifunensine was infiltrated in leaf tissue instead of being supplied hydroponically.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the study of kifunensine on whole-plant transient protein expression through agroinfiltration is new. There are only two published papers on whole-plant kifunensine treatment, where kifunensine was supplied hydroponically throughout the whole incubation period [ 15 , 16 ], which requires larger quantities of kifunensine, a more expensive hydroponic system and constant monitoring especially at large scale as compared to our method. In addition, it was also shown that hydroponic kifunensine treatment resulted in dramatic decrease of protein expression level [ 16 ] which was not observed with our method.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that massive synthesis and accumulation of a foreign protein in leaves would affect the physiology of the plant. Recent studies have shown that transient overexpression of a recombinant protein using a viral vector could cause severe stress, such as the endoplasmic reticulum (ER) stress, to N. benthamiana plants, leading to reduction in protein yield ( Hamorsky et al, 2015 ; Roychowdhury et al, 2018 ). Viral vector inoculation would also induce defensive responses of plants, including the hypersensitive response ( Lam et al, 2001 ; Mandadi and Scholthof, 2013 ) and systemic acquired resistance ( Fu and Dong, 2013 ), which affect plant physiology.…”
Section: Introductionmentioning
confidence: 99%